Behavior and Preparedness to Fire Hazard in High Density Settlements in Bandung - Sagala, Saut; Wimbardana, Ramanditya; Pratama, Ferdinand Patrick (Universitas Muhammadiyah Surakarta, 2014)
Fire is one of the hazards that may affect urban areas with high density settlements. Thus, research on fire mitigation is important to be conducted. This paper examines the behavior and preparedness of occupants in high density settlements towards fire risks in urban area. The case study is located at Kelurahan Sukahaji, Kecamatan Babakan Ciparay, Bandung that has very high density settlement as well as prone to fire hazards. This study assess 232 respondents in the study areas on information related to demography, understanding about fire, behavior and preparedness. The respondents understanding on the types of fire sources are still low. Similarly, the behavior related to the activites using fire are still dangerous because some activities are conducted with other activities which make people less aware of the fire hazards. Nevertheless, their knowledge on how to extinguish fires are quite good. This paper recommends more trainings on knowledge of fire source and behavior to be conducted to occupants living in high density settlements in order to reduce fire disaster risk.